Multicultural school psychology competencies a practical guide - Martines, Danielle; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2008)
This is a practical resource guide presenting lecturers and students with material which will help apply the theory of multicultural school psychology and counselling in practice. Its emphasis is on helping educational psychologists to develop and refine multicultural competencies and assessments.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: School psychologists; Minority students -- Counseling of; Electronic books